2018
DOI: 10.1101/486027
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Urinary AQP5 is independently associated with eGFR decline in patients with type 2 diabetes and nephropathy

Abstract: AQP5 has been shown to be upregulated in kidney biopsies from patients with diabetic nephropathy.Here we investigate whether urinary baseline AQP5 is independently associated with eGFR decline in patients with type 2 diabetes and nephropathy. Baseline urine samples (n=997) from patients with type 2 diabetes and nephropathy recruited in the Sun-MACRO randomized placebo controlled double blind clinical trial were used for AQP5 measurement, using human AQP5-specific enzyme linked immunosorbent kits. Pearson corre… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Upregulation of AQP-2 and -5 is closely related to the progression of diabetic nephropathy in diabetic patients and are good candidates to use for diagnosis [21,27]. Recently, Go and Zhang also reported that an increase in AQP-5 in patients with diabetic nephropathy is independently associated with a reduction in the glomerular ltration rate [28]. In addition, a STZ-induced diabetic rat model exhibits a high level of anti-diuretic hormone, leading to upregulation of AQP-2 as a compensatory mechanism [29].…”
Section: Discussionmentioning
confidence: 98%
“…Upregulation of AQP-2 and -5 is closely related to the progression of diabetic nephropathy in diabetic patients and are good candidates to use for diagnosis [21,27]. Recently, Go and Zhang also reported that an increase in AQP-5 in patients with diabetic nephropathy is independently associated with a reduction in the glomerular ltration rate [28]. In addition, a STZ-induced diabetic rat model exhibits a high level of anti-diuretic hormone, leading to upregulation of AQP-2 as a compensatory mechanism [29].…”
Section: Discussionmentioning
confidence: 98%
“…AQP5 is a possible marker of tubular dysfunction and its basal levels were analyzed in two studies: one with a limited number of samples from T2D and T2D with diabetic nephropathy patients and the second with almost 1000 urine samples from patients with T2D with diabetic nephropathy. Both the studies candidate AQP5 as a prognostic marker for diabetic nephropathy progression and suggest an association between AQP5 baseline expression and the estimated glomerular filtration rate (eGFR) [ 136 , 137 ].…”
Section: Possible Role Of Aqps “Metabolic Network” In Obesity-induced Systemic Insulin Resistancementioning
confidence: 99%